Congressman Tony Coelho Keynotes San Joaquin College of Law Graduation - Watkins, Howard::::::::: (1989)
Jim Petrucelli shaking hands with Justice Ardaiz; all smiling/laughing 1st row Seated: Hon. Hollis Best, ? Congressman Coelho and Oliver Wanger